2017
DOI: 10.1002/mus.25666
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary neuropathy with liability to pressure palsy in patients under 30 years old: Neurophysiological data and proposed electrodiagnostic criteria

Abstract: Dissemination of nerve involvement in HNPP incites to perform a complete nerve conduction study. including bilateral ulnar, fibular, and median nerves. Muscle Nerve 57: 217-221, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
5
0
4
Order By: Relevance
“…A recent study that involved HNPP patients under the age of 30 years showed demyelinating features in symptomatic and asymptomatic nerves, with the highest involvement in the ulnar, peroneal, and median nerves. Moreover, there was a significant prolongation of distal motor latency in the tested nerves with slow motor velocities [ 9 ]. Another study found a significantly accentuated distal slowing in the median and peroneal nerves with less involvement of ulnar and tibial nerves [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that involved HNPP patients under the age of 30 years showed demyelinating features in symptomatic and asymptomatic nerves, with the highest involvement in the ulnar, peroneal, and median nerves. Moreover, there was a significant prolongation of distal motor latency in the tested nerves with slow motor velocities [ 9 ]. Another study found a significantly accentuated distal slowing in the median and peroneal nerves with less involvement of ulnar and tibial nerves [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 A recent study suggests that diagnostic workup for suspected HNPP should include a complete nerve conduction study with a minimum of bilateral median, ulnar, and peroneal nerves independent of symptomology, due to typical generalization of nerve involvement. 7 Sonographic evaluation may be helpful in cases in which electrodiagnostic studies and genetic testing are unavailable or not completely consistent with HNPP, 8 likely unnecessary in this case as electrodiagnostic studies were highly suggestive. In terms of genetics, a contiguous gene deletion of chromosome 17p11.2 including PMP22 is found in approximately 80% of affected patients.…”
Section: Sectionmentioning
confidence: 95%
“…Neurophysiological studies demonstrate decreased motor nerve conduction velocities, prolonged distal motor latencies predominantly at sites of common nerve entrapment, and abnormal sensory nerve action potentials even in clinically unaffected nerves. 94,95 Genetic testing is available evaluating for PMP22 gene deletion; a recent study used next-generation sequencing-based copy number variation analysis to test asymptomatic newborns and found a genetic prevalence of 58.9 per 100,000, which is unsurprising given the combination of underdiagnosis and likely incomplete penetrance of the disease. 96 As for MADSAM, laboratory testing is similar to that for CIDP as detailed in a previous section.…”
Section: Acute Mononeuropathy or Multiple Mononeuropathiesmentioning
confidence: 99%